2021
DOI: 10.1186/s12991-021-00366-y
|View full text |Cite
|
Sign up to set email alerts
|

The factor structure and psychometric properties of the Chinese version of the Positive and Negative Suicide Ideation Inventory (PANSI-C) in a non-clinical sample of Chinese adolescents

Abstract: Backgrounds The Positive and Negative Suicide Ideation (PANSI) Inventory is a widely used self-report questionnaire which is designed to comprehensively evaluate the protective factors and negative risk factors associated with suicidal behaviors among adolescents. The present study aimed to evaluate the psychometric properties and measurement invariance of the Chinese version of the PANSI in a non-clinical sample of Chinese adolescents. Methods Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 45 publications
0
10
2
Order By: Relevance
“…Invariance results indicate that the PANSI has strong gender invariance in this population. Although these results are not as conclusive as the strict invariance found by Chen et al [27], these results are sufficient to make meaningful comparisons between groups, and it can be considered that they share the same operational definition [40]. There are various possible explanations for the differences between these and Chen et al's [27] results.…”
Section: Discussioncontrasting
confidence: 55%
See 4 more Smart Citations
“…Invariance results indicate that the PANSI has strong gender invariance in this population. Although these results are not as conclusive as the strict invariance found by Chen et al [27], these results are sufficient to make meaningful comparisons between groups, and it can be considered that they share the same operational definition [40]. There are various possible explanations for the differences between these and Chen et al's [27] results.…”
Section: Discussioncontrasting
confidence: 55%
“…Although reliability scores raise some concerns regarding Item 4 slightly raising the scale's α, the literature regarding the adolescent version of the PANSI shows that its items do not factor as well into their respective scales, as is the case with Avendaño-Prieto et al [25], who found that certain items tend to aggregate into a third factor. Additionally, regarding positive ideation's lower reliability, Chen et al [27] argue that non-clinical samples might have a harder time understanding some of the items relating to this subscale. These results, in addition to positive ideation's relatively low AVE, highlight the difficulty of assessing suicidal protective factors through self-report in non-clinical populations.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations